(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
This paper presents the results of an investigation into understanding of mathematical concepts among B.Ed students. Two hundred B.Ed. students were assessed for their understanding of mathematical concepts. The findings revealed that the B.Ed. students have adequate understanding of mathematical concepts and there was significant difference in the understanding of mathematical concepts among Male and Female B.Ed. students and there was no significant difference in the understanding of mathematical concepts of the Science and Arts B.Ed. students.